DIGITAL FINANCIAL INCLUSION AND BANK STABILITY IN A DUAL BANKING SYSTEM: DOES FINANCIAL LITERACY MATTER? - Banna, Hasanul (Bank Indonesia, 2025)
This study examines the relationship between digital financial inclusion (DFI), financial literacy, and stability of conventional and Islamic banks across 15 countries from 2011 to 2020. The findings show that DFI significantly enhances the stability of conventional banks, particularly through increased customer engagement with digital financial services, improving asset quality and reducing risks. In contrast, the relationship between DFI and stability of Islamic banks is either insignificant or negative, which may be attributed to Shariah compliance requirements, product mismatches, and competition from conventional banks and FinTech firms. Furthermore, while DFI boosts stability in conventional banks, it also exposes them to potential risks such as digital bank runs, as seen in the case of Silicon Valley Bank (SVB) in 2023. Additionally, high financial literacy positively interacts with DFI to boost the stability of conventional banks but has a negative impact on Islamic banks. Arguably, financially literate customers may resist digital services that do not fully meet Islamic principles. The results highlight the need for tailored strategies in Islamic banking, including the development of Shariah-compliant digital products, enhanced financial literacy programs, and more robust risk management frameworks to mitigate vulnerabilities like digital bank runs and improve stability in the sector.